2013
DOI: 10.1186/1471-2164-14-55
|View full text |Cite
|
Sign up to set email alerts
|

A colorectal cancer genome-wide association study in a Spanish cohort identifies two variants associated with colorectal cancer risk at 1p33 and 8p12

Abstract: BackgroundColorectal cancer (CRC) is a disease of complex aetiology, with much of the expected inherited risk being due to several common low risk variants. Genome-Wide Association Studies (GWAS) have identified 20 CRC risk variants. Nevertheless, these have only been able to explain part of the missing heritability. Moreover, these signals have only been inspected in populations of Northern European origin.ResultsThus, we followed the same approach in a Spanish cohort of 881 cases and 667 controls. Sixty-four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 40 publications
2
30
0
Order By: Relevance
“…Concerning the later, Fernandez-Rozadilla et al first reported the association of the rs8180040 variant and CRC in a GWAS performed in Spain. 19 According to the authors, the rs8180040 variant was inversely associated with CRC risk which is in agreement with the protective effect of the rs8180040 allele A against colorectal adenomas observed in our study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Concerning the later, Fernandez-Rozadilla et al first reported the association of the rs8180040 variant and CRC in a GWAS performed in Spain. 19 According to the authors, the rs8180040 variant was inversely associated with CRC risk which is in agreement with the protective effect of the rs8180040 allele A against colorectal adenomas observed in our study.…”
Section: Discussionsupporting
confidence: 92%
“…Over the last two decades, numerous association studies have been conducted in order to assess the relevance of common gene polymorphisms on CRC risk . However, the influence of gene variants in the development of colorectal adenomas and the role of CRC family history in this association has been scarcely analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mice engineered with myeloid-cell specific genetic deletion of Tnf AREs succumb to spontaneous inflammatory disease (Kontoyiannis et al, 2002; Kontoyiannis et al, 1999), in accord with the idea that NF-κB signaling and transcription of Tnf occur in the steady state and that post-transcriptional regulation by MAPK provides a critical second barrier to initiation of aberrant inflammation. GWAS have linked genes for MAPK-regulating phosphatases in the dual-specificity phosphatases (DUSP) family with IBD and colorectal cancer (Fernandez-Rozadilla et al, 2013; Houlston et al, 2010; Jostins et al, 2012; Yang et al, 2014), which are also associated with aberrant TNF production (Croft et al, 2013). It is interesting to speculate that impaired MAPK de-phosphorylation by DUSPs, due to quantitative trait loci–related changes in protein expression, may shift the MAPK dose-response towards the type of higher sensitivity we see in RAW macrophages.…”
Section: Discussionmentioning
confidence: 99%